2020
DOI: 10.3389/fphar.2020.00552
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Dosage Optimization of Teicoplanin in Children With Different Renal Functions

Abstract: Objective: The purposes of our study were to investigate the population pharmacokinetics of teicoplanin in Chinese children with different renal functions and to propose the appropriate dosing regimen for these pediatric patients.Methods: We performed a prospective pharmacokinetic research on children aged 0-10 years, with different renal functions. The population pharmacokinetics model of teicoplanin was developed using NLME program. The individualized optimal dosage regimen was proposed on the basis of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Gao et al reported dosing regimens for Chinese pediatrics to achieve the C min of > 10 mg/L. Three loading doses of 6–12 mg/kg every 12 h, followed by a maintenance doses of 8–10 mg/kg/day were required, which is similar to three loading doses of 10 mg/kg every 12 h, followed by a maintenance dose of 6–14 mg/kg/day in our study ( Gao et al, 2020 ). 2) Although antibiotic dosing as determined by PK/PD data was suggested, lack of practitioner familiarity, unclear benefit, time allocation and training requirements are the biggest obstacles to make it in clinical practice ( Kufel et al, 2019 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Gao et al reported dosing regimens for Chinese pediatrics to achieve the C min of > 10 mg/L. Three loading doses of 6–12 mg/kg every 12 h, followed by a maintenance doses of 8–10 mg/kg/day were required, which is similar to three loading doses of 10 mg/kg every 12 h, followed by a maintenance dose of 6–14 mg/kg/day in our study ( Gao et al, 2020 ). 2) Although antibiotic dosing as determined by PK/PD data was suggested, lack of practitioner familiarity, unclear benefit, time allocation and training requirements are the biggest obstacles to make it in clinical practice ( Kufel et al, 2019 ).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, it has been demonstrated that nearly 60% of children in pediatric intensive care unit (PICU) exhibit augmented renal clearance (ARC), resulting in low drug exposure due to enhanced excretion ( Van Der Heggen et al, 2019 ). Little is known about the PK of teicoplanin in children (eight studies in total), which greatly hinder the dosing optimization of teicoplanin in children, and only one of them involves Asian children ( Supplementary Table S1 ) ( Terragna et al, 1988 ; Reed et al, 1997 ; Aarons et al, 1998 ; Sanchez et al, 1999 ; Lukas et al, 2004 ; Ramos-Martin et al, 2014 ; Zhao et al, 2015 ; Gao et al, 2020 ). The objectives of this analysis were to: 1) determine the PK of teicoplanin in Asian children by using a population approach; 2) evaluate the standard dosage regimens of teicoplanin; and 3) establish a simulation-based dosage regimens in this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…Review of titles and abstracts led to the retrieval of 215 potentially relevant full‐text citations. After full‐text review, 25 citations met the criteria for inclusion 16–41 . The most common reason for exclusion was non‐pediatric population studies (190 citations), followed by lack of ARC data (24 citations).…”
Section: Resultsmentioning
confidence: 99%
“… 17 Since teicoplanin is mainly excreted by the kidneys, 27 impaired renal function usually causes a decrease of teicoplanin clearance. 28 In addition, drug clearance and volume of distribution in children also changed with the increase of age and weight, further affecting the drug exposure. Strenger et al found that compared with school-age children, young children had significantly lower initial teicoplanin C min .…”
Section: Discussionmentioning
confidence: 99%